Temperature-dependent Crystallization of MoS2 Nanoflakes on Graphene Nanosheets for Electrocatalysis - Xiaoru Guo; Yang Hou; Ren Ren; Junhong Chen (Nanoscale Research Letters, 2017)
Abstract This work primarily studies the crystallization condition of molybdenum disulfide (MoS2) in MoS2/graphene hybrids by a temperature-varying hydrothermal method from 150 to 240 °C. Flower-like MoS2 nanoflakes were successfully grown on graphene nanosheets and characterized to understand the temperature-dependent crystallization process and the electrochemical performance. The highest electrocatalytic efficiency for both the dye-sensitized solar cell and the hydrogen evolution reaction was obtained by preparing the hybrid at 180 °C, which benefits from balanced high reactivity and high conductivity. This research leads to a better understanding of temperature dependence of MoS2 crystallization and offers guidelines for better catalytic material design. Graphical abstract Temperature-dependent Crystallization of MoS2 Nanoflakes on Graphene Nanosheets for Electrocatalysis